Biased and unwarranted Political view in Lancet Journal - Joshi, Krupal; Singhal, Sanjay; Dhariwal, Akshay; Tandon, Ashwani (Indian Journal of Community Health, 2024)
<div class="min-h-[20px] text-message flex flex-col items-start whitespace-pre-wrap break-words [.text-message+&]:mt-5 juice:w-full juice:items-end overflow-x-auto gap-2" dir="auto" data-message-author-role="assistant" data-message-id="63decec6-d213-40ce-9796-65d5d0513df3"> India is the largest democratic country and currently celebrating the festivity of the election. We observed that the editorial by Lancet published about India’s election: Why Data and Transparency Matter (1). After reading the editorial, the most important question came to the mind of Indian readers: Is there any hidden agenda in the editorial team of Lancet Journal? Why did the Lancet choose to deal with the subject of data and transparency at the time of the election in India? Close examination of this editorial’s references, particularly the second one, confirmed the hunch of readers that the comprehension is significantly biased as it is based on a media report and the editor has used his position in a scientific journal to interfere in the affairs of a sovereign nation. It is totally unacceptable and undone of scientific temperament. Through this letter, our team is conveying the feelings of the people of the largest democratic and secular country. We would not pick the Lancet as our first source of information on this issue. Secondly, the journal cannot afford to become politicized by allowing only one point of view to be expressed. How will we know the editor hasn't rejected papers simply because their findings disagree with your politics?